CHARACTERIZATION OF DOMINATING BACTERIAL SPECIES IN POTABLE WATER - PAVAN KUMAR PINDI; K. ASHWITHA; P. SANDHYA; B. SWAPNA; R. AMBIKA; P. RAGHUVEER YADAV (International Journal of Pharma and Bio Sciences, 2013)
This paper aims at the analysis of diversity of bacteria found in samples of potable water. Expanding access to water and sanitation is moral and ethical imperative rooted in the communities around the world. Over one billion people lack access to safe drinking water. Safe drinking water and basic sanitation is of crucial importance to the preservation of human health, especially among children. Microbial contamination of water has long been a concern to the public. It is necessary to provide sufficient information to control microbiological quality of potable water sample collection was carried out in 13 different places of Mahabubnagar district, Andhra Pradesh, India which was followed by isolation, multiplication and bacterial identification as a result of which revealed 33 different morphotypes which belonged to both gram positive and gram negative bacteria. The study is employed basing on morphological, biochemical tests, antibiotic sensitivity tests and 16S rRNA gene approach to identify the active bacterial communities. Of the 33 different morphotypes, only 4 dominating species were considered for further studies. The most common groups identified were Enterobacter (E.cloacae, E.cancerogenus, and E.hormaechei) and Bacillus (B.firmus). On the whole, biochemical tests, antibiotic tests and 16S rRNA gene sequencing suggest that these active bacterial groups are dominant in the potable water.